The sound framework of parameter mapping in sonifying 3d hands movements - Ag Asri Ag Ibrahim; Alter Jimat Embung; Ryan Macdonell Andrias; Soffri Yussof (American Scientific Publishers, 2018)
In physiotherapy, most of instructions by trainers or physiotherapists in body movements are normally done through voice instructions or touches. To follow these instructions without seeing it is not easy especially for blind people. It is hoped by listening to non-speech sounds as an alternative of medium of instructions; a person should be able to follow the exact body movements. Thus, this paper explains the potential of using non-speech sound to represent 3D hand movements. In this research, the conversion of data-to-sound technique was using Parameter Mapping, where the movement coordinates were mapped with sound properties. Series of experimental design have been carried out and the results will be discussed.